Retrospective study of post-operative care in pandemic in tertiary care centre - Roshini, E.; Indu, N. R.; Banu, A. Shameera; Hiremath, P. B.; Hiremath, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: COVID-19 pandemic has unfortunately changed the surgical interventions and the post-operative management worldwide. Most of the medical institutes in India had formulated their own protocols from the beginning of the pandemic in March 2020 to stop all elective surgical procedures as soon as possible. However emergencies and all types of obstetric as cases were not stopped as it was unavoidable conditions. Methods: This retrospective observational study was done in the department of obstetrics and gynaecology, at Sri Venkateshwaraa Medical College, Ariyur, Puducherry, during the period April 2020-December 2020. Data was collected from the case sheets and operative notes and retrospective analysis was done. Results: On analysing we have realised that LSCS rate was higher and induction for trial of labour was kept minimal. We had 3 infective morbidity in the form of wound infection and 1 patient was returned to the operation theatre for reexploration. Arranging the blood during the pandemic was also a tedious task. Conclusions: In the present era of pandemic, where the patient load is high, we can rely on post graduate students to look after the post-operative patients through effective communication with the available consultants.